Pathophysiology, physical assessment, and pharmacology : advanced integrative clinical concepts - Best, Janie T.; Buttriss, Grace; Hines, Annette (Philadelphia : F.A. Davis Company, 2022)
'This groundbreaking textbook, Pathophysiology, Physical Assessment, and Pharmacology: Advanced Integrative Clinical Concepts, facilitates knowledge in a way that enables student understanding for real world application. Integrating the concepts of physiology/ pathophysiology, physical assessment, and pharmacology eliminates the silo approach to nursing education and guides the student to explore how each element impacts the other'--
Hypertension -- Diabetes Mellitus -- Obesity -- IBS and IBD -- Myocardial Infarction -- Case Study 1 (Adult) : Glaucoma -- Hypertensive Disorders of Pregnancy -- Gestational Diabetes -- High-Risk Pregnancy -- Gastrointestinal Conditions -- Case Study 2 (Maternity) : Vaginal Bleeding -- Hyperbilirubinemia in the Newborn -- Congenital Heart Disease -- Respiratory Conditions -- Prematurity and Newborn Conditions -- Case Study 3 (Newborn) : Nutrition -- Asthma -- Allergic and Hypersensitivity Disorders -- Gastroesophageal Reflux Disease -- Traumatic Brain Injury -- Otitis Media -- Case Study 4 (Pediatrics) : Acute Lymphoblastic Leukemia -- Healthy Aging -- Heart Failure -- Pneumonia -- Osteoarthritis and Rheumatoid Arthritis -- Chronic Kidney Disease -- Case Study 5 (Geriatric) : Osteoporosis -- Altered Cognitive Function -- Anxiety and Depression -- Psychotic Disorders -- Substance Abuse Disorders -- Case Study 6 (Mental Health) : ADHD.
Includes bibliographical references.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Added to collection customer.56279.3
Keywords: Nursing; Nursing Process; Nursing Care; Nursing; Soins infirmiers -- Démarche.; Soins infirmiers; nursing (health science); Nursing